Adipose tissue quantity and composition contribute to adipokine concentrations in the subclavian vein and the inferior mesenteric vein - Faber, D R; Moll, F L; Vink, A; van der Waal, C; Kalkhoven, E; Schipper, H S; Hajer, G R; Monajemi, H; Visseren, F L J (International Journal of Obesity, 2012)
BACKGROUND: Adipose tissue dysfunction is associated with inflammation, type 2 diabetes mellitus and vascular diseases. Visceral adipose tissue (VAT)-derived adipokines, which are released in the portal circulation may influence liver metabolism. OBJECTIVES: (1) To estimate the contribution of VAT and subcutaneous adipose tissue (SAT) on adipokine levels by measuring differences in adipokine concentrations between the portal draining inferior mesenteric vein and the subclavian vein. (2) To determine the relation of both VAT and SAT quantity and composition to mesenteric and systemic concentrations of adipokines. DESIGN: Cross-sectional cohort study. SUBJECTS: A total of 32 patients undergoing abdominal aortic surgery. MEASUREMENTS: A panel of 18 adipokines was measured in perioperatively obtained blood samples from the subclavian vein and the inferior mesenteric vein. Adipocyte size, macrophage infiltration and capillary density were measured in subcutaneous and mesenteric adipose tissue biopsies; SAT and VAT areas were measured on computed tomography images. RESULTS: Serum interferon-γ-inducible protein 10 (IP-10) and hepatocyte growth factor (HGF) concentrations were significantly higher in the inferior mesenteric vein vs the subclavian vein. SAT area (β –18; 95% confidence interval (CI) −35 to −2), subcutaneous adipocyte size (β –488; 95% CI −938 to −38) and SAT macrophages quantity (β –1439; 95% CI −2387 to −491) were negatively associated with adiponectin levels in the systemic circulation. SAT area was related to systemic concentrations of leptin. Mesenteric adiponectin concentrations were related to VAT area (β –20; 95% CI −35 to −5) and visceral adipocyte size (β −1076; 95% CI −1624 to −527). VAT area, adipocyte size and capillary density were related to systemic adiponectin concentrations. CONCLUSION: SAT and VAT quantities as well as morphologic characteristics of both adipose tissue depots are related to systemic and mesenteric adipokine concentrations. There were no differences in adipokine concentrations between the mesenteric and subclavian vein, except for higher IP-10 and HGF concentrations in the inferior mesenteric vein, indicating a possible contribution of VAT to IP-10 and HGF levels.